Industrial physics / Nor Fadzilah Ahmad Tarmizi …[et al.] - Ahmad Tarmizi, Nor Fadzilah; Kamaluddin, Nuradnin; Dee, Norsyazanim; Abd Rahman, Siti Sarah; Roslan, Nik Raudhah (2016)
Banana Green Enterprise is a company that venturing into environmental sustainability technology. We are specialized in making environmental friendly papers that is giving benefit to both costumers and the environment. Our product, BG papers, is a product that was produced based on invasive research from agricultural waste. The uniqueness of our paper lies in the technology of processing the paper that uses less harmful chemical to human and environment. We use the best quality of banana stem that is harvested from local people as the main raw material in our product. Our major advantage is the production of the paper is very safe, since we do not have to deal with any sharp, or pointy wood barks, we also do not involve with any chippings that escape from the wood cutter. Our productions are also uses only gentle chemical such as NaOH that I very easy to treat and doesn't cost much. Our company is located in Shah Alam, and actively supplying our products to the retailers and Shopping Mall. Our product is very versatile as it can be used in any machines such as Photocopy machines, fax or laser jet printer. Overall, we are producing a paper that has the same quality like any conventional wood paper, but, with less adverse impact to environment. We hope that our product can be widely accepted by the society because our product has provided the solution for the depleting resource of wood and land with a paper that can be generated from waste. In future, we hope to embark in much wider range of environmental friendly products and become the leading company in environmental tech based products